A racionalidade instrumental e substantiva nas práticas de formação do administrador: Um estudo de casos múltiplos junto a instituições de ensino em Curitiba - Hey, Lucinete Aparecida Nava (2008)
The increasing offer of higher degree education, the invigoration and the globalization of the economy have demanded a deeper reflection from the economic and social agents over the last years. In this context, the matter concerning the education of the manager cannot be disconnected from the debates, once the entrepreneurial efficiency and personal fulfillment are not direct consequences of the managers’ actions. The changes in the worldwide scenario instigate the universities to pursue the adaptation to new requirements of the companies and the social environment. Following the reasoning of other researches regarding the substantive rationality, but, instead, focusing the academic education, the present research aims to verify how the instrumental and substantive rationalities are present in the education of the manager in the City of Curitiba. By means of the analysis of multiple cases, the present study approaches the rationalities present in the educational practices of the higher education institutions, analyzing the form by means of which said rationalities contribute to the social changes. In order to attain said objectives, bibliographic research techniques, simple observation, semi-structured interviews and focus-group were used. Based on the studies of instrumental and substantive rationalities of Guerreiro Ramos and Mauricio Serva and on the research executed with professors and students, it was possible to determine the analysis categories that guide the research, thus executing the data triangularization to understand the conception of educational practices of all involved in the investigation. By means of the delimitations established by the research, it was possible to verify that the manager formation practices used by the universities contain elements both of the instrumental and the substantive rationality. Even considering the tensions between the logic centered in the market and the logic centered in the human aspect, it is possible to identify substantive values by means of the spaces of human interaction, where the professors, aware of their actions, contribute to the development of social values. The research also intends to draw attention upon the importance of the rationalities present in the universities as an instrument to development of actions which may contribute to the social changes.